PENDIDIKAN KESEHATAN OBESITAS PADA REMAJA DI LINGKUNGAN SMA SAINS TAHFIZH ISLAMIC CENTER SIAK - Agus Salim; Devi Purnamasari; Sherly Mutiara (Awal Bros Journal of Community Development, 2024)
Obesity is still a very serious problem in Indonesia, one of which is in children's lives, many children experience limited movement, inhibiting physical motor development so that physical motor development in children will be disrupted. Improper eating patterns are one of the main factors that cause nutritional problems in children. By looking at the facts that are happening now, many Indonesian people prefer fast food or fast food and foods and drinks that contain high amounts of processed sugar. Therefore, the author conducted outreach and distributed posters to prevent obesity in teenagers at the Tahfidz Islamic Center Siak Science High School. The aim of this community service is to increase teenagers' knowledge about obesity prevention and increase knowledge of the dangers of obesity. This community service activity was carried out in the Tahfidz Islamic Center Siak Science High School classes. The results of this counseling or outreach can increase knowledge for young students at the Tahfidz Islamic Center Siak Science High School about the prevention and impacts of obesity.